2012
DOI: 10.5732/cjc.011.10376
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo expansion of tumor-infiltrating lymphocytes from nasopharyngeal carcinoma patients for adoptive immunotherapy

Abstract: Establishing Epstein-Barr virus (EBV)-specific cytolytic T lymphocytes (EBV-CTLs) from peripheral blood mononuclear cells (PBMCs) for adoptive immunotherapy has been reported in EBV-associated malignancies including Hodgkin's lymphoma and nasopharyngeal carcinoma (NPC). In the current study, we performed ex vivo expansion of tumor-infiltrating lymphocytes (TILs) obtained from NPC biopsy specimens with a rapid expansion protocol using anti-CD3 monoclonal antibody (OKT3), recombinant human interleukin (IL)-2, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…Immunosuppression mediated by Tregs is a key facilitator of tumor immune evasion [30], [42], [43]; however, knowledge of the phenotypic characteristics of tumor-associated Tregs in human tumors remains limited [44], [45]. In the current study, we demonstrated that Tim-3 can serve as a novel surface marker to define tumor-infiltrating Tregs.…”
Section: Discussionmentioning
confidence: 60%
“…Immunosuppression mediated by Tregs is a key facilitator of tumor immune evasion [30], [42], [43]; however, knowledge of the phenotypic characteristics of tumor-associated Tregs in human tumors remains limited [44], [45]. In the current study, we demonstrated that Tim-3 can serve as a novel surface marker to define tumor-infiltrating Tregs.…”
Section: Discussionmentioning
confidence: 60%
“…The outgrowth of antigen-loss tumour variants in treated patients indicates the ability of rapidly adaptable tumour cells to evade narrowly focused therapies (Mellman et al , 2011; He et al , 2012). Recently, new therapies based on sophisticated knowledge of the suppressive tumour immune microenvironment were designed to overcome tolerance and reactivate anti-tumour immunity to induce potent, long-lasting responses (Mellman et al , 2011).…”
Section: Discussionmentioning
confidence: 99%
“…26 A phase I immunotherapy trial of adoptively transferred TILs has been performed on 23 NPC patients with locoregionally advanced NPC following concurrent chemoradiotherapy. Furthermore, TILs from NPC biopsy specimens have been reported to be cultured ex vivo and used as a T-cell-based immunotherapy for NPC patients.…”
Section: Tumor Markers and Signaturesmentioning
confidence: 99%